Standardized Herbal Extract for Wound Healing: A Comparative Study of Centella asiatica, Curcuma domestica, and Heterotrigona itama Honey Combination in Rabbits - Diniatik, Diniatik; Kustiawan, Paula Mariana; Suryadini, Halida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Centella asiatica and Curcuma domestica are recognized for their wound-healing properties. This study investigated the synergistic effects of combining these plant extracts with stingless bee (Heterotrigona itama) honey on wound healing in rabbits. Ethanolic extracts of C. asiatica and C. domestica were prepared in a 1 : 10 ratio. Blended formulations containing 20% plant extracts and 80% honey were created in two ratios: 1 : 1 and 2 : 1. The total flavonoid and tannin content of the plant extracts were quantified. Male rabbits were subjected to a wound-healing model, and the formulations were applied topically for seven days. Wound healing was assessed, and the results were compared to a positive control. The ethanolic extracts of C. asiatica and C. domestica were rich in flavonoids and tannins. The blended honey formulations exhibited promising wound-healing effects, with Formula 2 (2 : 1 ratio of plant extracts) demonstrating slightly superior results compared to Formula 1 and the positive control. These findings suggest the potential of the combined extracts of C. asiatica, C. domestica, and H. itama honey as effective wound-healing agents.